A study of hearing function and histopathologic changes in the cochlea of the type 2 diabetes model Tsumura Suzuki obese diabetes mouse. - Junko Tsuda; Kazuma Sugahara; Takeshi Hori; Eiju Kanagawa; Eiichi Takaki; Mitsuaki Fujimoto; Akira Nakai; Hiroshi Yamashita (Acta Oto-Laryngologica (Supplement), 2016)
Objectives: This study used Tsumura Suzuki Obese Diabetes (TSOD) mice as a spontaneous type 2 diabetes model and Tsumura Suzuki Non-obesity (TSNO) mice as controls to investigate factors involved in the onset of hearing impairment. Method: Body weight, blood glucose levels, and auditory brainstem responses (ABRs) were measured. The cochleae were excised and evaluated histopathologically. Results: The TSOD mice showed significant hyperglycemia at 2-7 months and severe obesity at 5-10 months; significantly elevated ABR thresholds at 8-10 months; and the capillary lumens in the cochlea stria vascularis were narrower in the TSOD mice than in the TSNO mice. At 17 months, India ink vascular staining of the TSOD mice's cochleae revealed decreased capillary density in the stria vascularis. The vascular area of capillaries in the stria vascularis and the vascular area were significantly smaller in TSOD mice. Histopathological analysis showed vessel wall thickening in the modiolus and narrowed capillaries in the stria vascularis, suggesting reduced blood flow to the inner ear. Conclusion: The diabetes mice model used in our study showed early age-associated hearing loss, and histopathology showed findings of vessel wall thickening in the modiolus, narrowing of capillaries in the stria vascularis, and chronically reduced blood flow in the cochlea.